2018
DOI: 10.1371/journal.pone.0193015
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of tumor associated macrophages in different tumor models

Abstract: Tumor progression largely depends on the presence of alternatively polarized (M2) tumor-associated macrophages (TAMs), whereas the classical M1-polarized macrophages can promote anti-tumorigenic immune responses. Thus, selective inhibition of M2-TAMs is a desirable anti-cancer approach in highly resistant tumor entities such as hepatocellular carcinoma (HCC) or breast cancer. We here examined whether a peptide that selectively binds to and is internalized by in vitro-differentiated murine M2 macrophages as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…populations including dendritic and epithelial cells that also express IL-1β and are potentially not affected through BTK inhibition. [36][37][38][39] However, further studies are needed to further investigate this hypothesis. Although the 4T1 model of breast cancer has substantial levels of neutrophils, this model has been utilized previously to study TAM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…populations including dendritic and epithelial cells that also express IL-1β and are potentially not affected through BTK inhibition. [36][37][38][39] However, further studies are needed to further investigate this hypothesis. Although the 4T1 model of breast cancer has substantial levels of neutrophils, this model has been utilized previously to study TAM.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 4T1 model of breast cancer has substantial levels of neutrophils, this model has been utilized previously to study TAM. 36,[40][41][42] Specifically, Makela et al demonstrated that cell tracking approaches can be utilized to visualize TAM in vivo using the 4T1 model. 43 NLRP3 expression within the tumor was not altered by the BTK inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study using HCC cells has studied M2pep binding also to TAMs, showing selectivity for M2-type macrophages. The authors also reported about M2pep binding to KCs, though binding to TAM was higher in comparison [ 96 ]. In summary, specific targeting to liver macrophage populations has been proven to be very challenging though extremely necessary to achieve different therapeutic objectives such as NP accumulation for specific drug delivery to induce or avoid immune responses or to modulate M1/M2 macrophage balance.…”
Section: Npc Populations Of the Liver Contribute To Its Tolerogenimentioning
confidence: 99%
“…The apparent TAM specificity of UNO may depend on a modification of the peptide that only happens on the surface of TAMs. Cieslewicz M. et al used cultured macrophages differentiated into the immune-suppressive M2 phenotype to isolate a peptide that shows a preferential binding to TAMs [20,21]. However, the receptor for this peptide has not been identified, which prevents the understanding of its TAM-targeting mechanism.…”
Section: Introductionmentioning
confidence: 99%